Water Aerobic Exercise Improves Mother’s Quality of Life During Pregnancy: A Systematic Review - Ayubi, Novadri; Putri, Dhea Regita Sastika; Syafawi, Atika; Aljunaid, Mohammed; Ming, Jiang Wen; Lesmana, Heru Syarli; Dafun, Procopio B. (Physical Education Theory and Methodology, 2024)
Objectives. This study aimed to analyze the effectiveness, benefits and safety of water aerobic exercise in improving the quality of life of pregnant women from a psychological and physical perspective. Materials and methods. The present study is defined as a type of systematic review research using searches from journal databases such as MEDLINE-PubMed, Web of Science, Scopus and Science Direct. The inclusion criteria for this study were articles published in the last 5 years and articles discussing pregnancy, aquatic aerobic exercise and quality of life in pregnancy. A total of 53 articles from the Science Direct, PubMed, and Web of Science databases were identified. A total of 8 articles that met the inclusion criteria were selected and analyzed for this systematic review. For standard operations, this study followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) assessment. Results. The findings of this systematic review indicate that participating in aquatic aerobic exercises has been found toreduce pain during labour, reduce the use of epidural analgesics during labour, reduce depression during pregnancy, reduce the risk of fetal distress, stabilize blood pressure, reduce back pain, and improve the psychological condition of pregnant women. Conclusions. The regular practice of water aerobic exercise carried out from the 2nd trimester of pregnancy contributes to having a positive impact on improving the quality of life of pregnant women.